2022
DOI: 10.19184/semiotika.v23i1.24367
|View full text |Cite
|
Sign up to set email alerts
|

Ekoleksikon Burung Merpati Sebagai Suplemen Pembelajaran Bahasa Berbasis Lingkungan: Perspektif Ekolinguistik

Abstract: Ecolinguistics diversity becomes the richness of language, especially in lexicon, grammatical and metaphorical expressions that function to preserve their living environment. The purpose of the research is as a strategic effort to keep the local language based on the environment. This research is essential because the various terms used in the speech community of the Banyumas pigeon lover community can be used as an additional for environmental-based language learning. The method is a qualitative by using an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Many ecolinguistic studies have been conducted, including, (Tiani, 2020), he concluded as a symbol of human harmonization with nature for agricultural lexicon, the collection of an area such as coastal areas is associated with religious rituals. However, due to globalization, it can be seen that the shift and survival of a language's lexicon, a new ecolexicon can emerge (Nurdiyanto et al, 2022). This can lead to the loss of use of the old lexicon and other lexicons that collocate with the old lexicon (Reniwati & Khanizar, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Many ecolinguistic studies have been conducted, including, (Tiani, 2020), he concluded as a symbol of human harmonization with nature for agricultural lexicon, the collection of an area such as coastal areas is associated with religious rituals. However, due to globalization, it can be seen that the shift and survival of a language's lexicon, a new ecolexicon can emerge (Nurdiyanto et al, 2022). This can lead to the loss of use of the old lexicon and other lexicons that collocate with the old lexicon (Reniwati & Khanizar, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…How can we use local language and knowledge to increase the resilience of agricultural ecosystems? Apart from changes in the environment and culture of the local community, language change does not occur at the lexicon level (Nurdiyanto et al, 2022). According to Mühlhäusler (1996), lexicons can develop, be preserved, develop, move, disappear, die, or even be standardized due to the influence of ecological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Dalam hubungannya dengan bahasa nasional, "bahasa daerah berfungsi sebagai penunjang bahasa nasional, bahasa Indonesia," (Dariono, 2021). Dengan demikian, bahasa daerah tidak hanya berfungsi sebagai penanda identitas daerah tetapi juga sebagai acuan dalam memperkaya khazanah bahasa nasional (Azmi, 2021;Nurdiyanto, et. al., 2022;Saputra dan Fitri, 2020).…”
Section: Pendahuluanunclassified
“…These expressions are Hadirman functional to protect the natural environment (Mardikantoro 2016). This expression with ecological nuances can become a memory for the community in protecting the environment and encodes the cultural diversity behind it (Nurdiyanto, Resticka, and Yanti 2022).…”
Section: Introductionmentioning
confidence: 99%